Culture modes and financial evaluation of two oleaginous microalgae for biodiesel production in desert area with open raceway pond. (October 2016) - He, Qiaoning; Yang, Haijian; Hu, Chunxiang
Highlights: Five microalgae were analyzed for their growth, lipid accumulation and FA profiles. Chlorella sp. L1 and M . dybowskii Y2 were selected for scale-up culture. Batch and semi-continuous mode were used in outdoors raceway pond. Lipid productivity of 13.91 and 14.45 ton ha −1  yr −1 in semi-continuous mode. 13.31 and 14.18 $ gal −1 for crude biodiesel in two microalgae were obtained. Abstract: Cultivation modes of autotrophic microalgae for biodiesel production utilizing open raceway pond were analyzed in this study. Five before screened good microalgae were tested their lipid productivity and biodiesel quality again in outdoor 1000 L ORP. Then, Chlorella sp. L1 and Monoraphidium dybowskii Y2 were selected due to their stronger environmental adaptability, higher lipid productivity and better biodiesel properties. Further scale up cultivation for two species with batch and semi-continuous culture was conducted. In 40, 000 L ORP, higher lipid productivity (5.15 versus 4.06 g m −2  d −1 for Chlorella sp. L1, 5.35 versus 3.00 g m −2  d −1 for M . dybowskii Y2) was achieved in semi-continuous mode. Moreover, the financial costs of 14.18 $ gal −1 and 13.31 $ gal −1 for crude biodiesel in two microalgae with semi-continuous mode were more economically feasible for commercial production on large scale outdoors.